FRI0120 The Incidence of Herpes Zoster (HZ) in A Population of Patients with Inflammatory Arthritis: A 12-Year Analysis from The Rhumadata Clinical Database and Registry. (15th July 2016) - Haraoui, B.; Bessette, L.; Brown, J.; Coupal, L.; Massicotte, F.; Pelletier, J.-P.; Raynauld, J.-P.; Rémillard, M.-A.; Sauvageau, D.; Villeneuve, Έ.; Choquette, D.
Abstract : Background: Herpes Zoster (HZ) is caused by the reactivation of the varicella zoster virus. It is more prevalent in older populations. Post-herpetic neuralgia, defined as pain lasting longer than 90 days post-eruption, is the most common serious complication of HZ. Immunosuppression from any cause including immunosuppressive treatments increases the risk by a minimum of ten times. Vaccination against HZ in patients with auto-immune diseases appears to be safe and effective 1 . Objectives: To describe the 12-year incidence of HZ in a population of patient with either rheumatoid arthritis (RA), ankylosing spondylitis (AS) or psoriatic arthritis (PsA) with and without any biologic treatment. Methods: All treatment episodes of patients with RA, AS, or PsA recruited in the RHUMADATA database from January 1, 1998, to October 1, 2015, were included in the analysis. All episode of HZ as reported by the patient to the healthcare provider were tabulated. Two cohorts were created. Patients with AS and PsA were pooled, and RA patients were analysed separately. Demographics included age, gender and disease duration. Data on exposure biologic agents, nbDMARDs, and to recent corticosteroid use (90 days before HZ or censoring) were also extracted. The incidence rates of HZ were estimated in biologic exposed and naïve patients from both cohorts. Univariate and multivariate Cox models were used to assess the relationship between age, biologic, nbDMARD and recent corticosteroid use, and the development of HZ. Results: RA patients (n=3431) were mostly women (77%) while AS/PsA patients (n=1, 727) were mostly men (55%). RA patients were older than AS/PsA patients (53.3 years (SD=12.6) vs. 45.4 years (SD=12.1)) and also had longer disease duration (5.5 years (SD=8.5) vs. 4.8 years (SD=25.1)). Thirty-six and 119 HZ episodes were observed in the AS/PsA and RA cohorts respectively. Among AS/PsA patients, the incidence rate of HZ per 100 patient-years was 0.80 (95% CI=0.53–1.16) among patients taking biologics and 0.29 (0.12–0.56) for biologic naïve patients (p-value=0.0071). The incidence rate of HZ among biologics treated RA patients was 1.08 (0.83–1.37) per 100 patient-years and 0.55 (0.41–0.72) among biologic naïve patients (p-value=0.0002). Overall, RA patients and AS/PsA patients had similar HZ incidence rates (0.62 (0.52–0.73) vs 0.53 (0.37–0.71), p-value=0.3460). The hazard ratios for "biologic use" among RA and AS/PsA patients were estimated at 1.866 (1.275–2.733) and 3.467 (1.529–7.859) respectively, after adjusting for age at treatment initiation, concurrent use of nbDMARDs and recent corticosteroid use. Conclusions: Biologic agents doubled the risk of HZ episodes in RA and AS/PsA patients. Significant predictors of HZ episodes among RA patients included age and use of biologics. Among AS/PsA patients, use of biologics and recent use of corticosteroids were significantly associated with the development of HZ. HZ immunization should be considered in patients before initiating biologic agents. References: Background paper on herpes zoster vaccines- SAGE working group accessed from the WHO website on: 07DEC2015. Disclosure of Interest: None declared